Polityka oświatowa władz w procesie instalowania nowego ładu społecznego (1944–1948) - Kahl, Edyta (Biuletyn Historii Wychowania, 2011)
The problems discussed in the article concern the educational policy in Poland in the first years after World War II (1944-1948). The article presents the educational concepts and postulates of different political fractions and teachers’ circles, which already before the end of the War had formulated their own educational programmes. The discussions about the shape of the post-war educational system, particularly the organization of schools, the school structure, the ideological foundations, the syllabus, school handbooks and teachers’ training, were carried out, among others, between the representatives of the National Democrats, Christian-national groups, political parties, teachers’ organizations and school administration. Their attitudes to many problems varied considerably, and thus, the situation required social debate and confrontation of opinions. The quality of those discussions, the style in which the educational problems were solved as well as the direction of the structural and ideological transformations in the post-war educational system, were significantly influenced by the geopolitical post-war conditions and a strong position of the Left, consolidated by the Soviets, in the policy of the Polish state. In the expansive struggle for the political leadership in Poland, the Left used different forms of pressure and terror in order to eliminate the opposition. To achieve social legitimization for its pseudo-democratic activities, the Left undertook attempts to encourage other groups to co-operate. Particularly, the communists tried to attract cultural elites, including teachers, who they wanted to use to start the process of rebuilding social consciousness according to the rules of the ideology of Marxism and Leninism. These monopolistic ambitions, in the first years after World War II, were reflected in the destruction of the underground state and the development of administrative structures of the totalitarian system. As far as the educational system is concerned, the policy of the Left was manifested in more and more apparent actions taken to subordinate school to the communists’ interests, thus including education into the process of the transformation of the political system. All those activities, were part of the phenomenon of structural Sovietization, formed the foundations for the ideological offensive, planned by the communists and conducted on a massive scale after the formation, in 1948, of the monopolistic Stalinian party - PZPR (Polish United Workers’ Party).